SERVICE MANAGEMENT BY THE DEPARTMENT OF ARCHIVES AND LIBRARY SUKABUMI DISTRICT IN REALIZING EDUCATIONAL TOURISM - Septiawan Maliki Barkah; Ike Rachmawati; Yana Fajar FY Basori (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
Public interest in reading is a major problem nationally and globally. One of the obstacles to the progress of a nation can be judged by the habits of its people in terms of reading. Reading is an important part of life. The Archives and Libraries Office of Sukabumi District continues to encourage the growth of interest in reading in the community by implementing programs and improving services to meet the needs of users. This research uses one variable (1), namely the service management variable, with A.S. Moenir's service management theory (2006: 88–119), which consists of indicators of awareness, rules, organization, income, skills and abilities, and service facilities. This study uses a qualitative method with a narrative approach. The results showed that the Sukabumi District Archives and Libraries Service had made significant efforts to manage quality services. They provide easy access to relevant information and libraries by facilitating the needs of the user. This service includes programs that support the improvement of human resources and collections of books, magazines, journals, and other media that are well managed and available to the public and visitors.